Partnerskabsmodellen: - Undersøgt i kurset Klimatilpasning og Planlægning - Jacobsen, Lulu (Improving University Science Teaching and Learning, 2023)
Resumé: The current trend in university policy seems to be positioning the university as an environment for learning distinct from its traditional role of knowledge transmission. This assignment poses the question: How can the partnership-model - that can be connected to this trend - be described and used in the specific course ´Climate Change Adaption and Planning´ – and which advantages and challenges does it imply? To answer this question I have adjusted my course to a more learning-centeret action plan and included more student activities. I have also sharpened my own attitude towards the students and spent time explaining my teaching intensions, having a lot of dialogue about their and mine expectations and facilitating their learning in a process stream approach. The conclusion is that the partnership-model has worked very well in this course, the students were very satisfied with the course and expressed to have gained many of the intended competencies. They performed very well at the summative assessment, which is not a goal in its self, but still an indication. I have become more aware of how to create a holistic approach towards the course alignment by using activities that support each other and the partnership-idea. I have also experienced how a learning-centered action plan is able to lead to educational output. This experiment has given me a greater awareness of how to create an atmosphere, that makes the students see university as providing a partnership to develop a culture of curious deep learners rather than a ´school with teachers´ who are supposed to guide, direct and evaluate them.